2019
DOI: 10.48550/arxiv.1909.10287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mean Field approach to stochastic control with partial information

Abstract: The classical stochastic control problem under partial information , as , for instance , described in the book of A. Bensoussan[2] , can be formulated as a control problem for Zakai equation, whose solution is the unnormalized conditional probability distribution of the state of the system, which is not directly accessible. Zakai equation is a stochastic Fokker-Planck equation. Therefore, the mathematical problem to be solved is very similar to that met in Mean Field Control theory. Since Mean Field Control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, in Féron et al (2020), it has been shown that explicit solutions may be found in the mean field limit, where the number of agents is sent to infinity, and the influence of every single agent on the entire market becomes negligible. The use of mean field theory for stochastic control with partial information has also recently been proposed by Bensoussan and Yam (2019), in a formal fashion, in order to solve the associated Zakai equation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in Féron et al (2020), it has been shown that explicit solutions may be found in the mean field limit, where the number of agents is sent to infinity, and the influence of every single agent on the entire market becomes negligible. The use of mean field theory for stochastic control with partial information has also recently been proposed by Bensoussan and Yam (2019), in a formal fashion, in order to solve the associated Zakai equation.…”
Section: Introductionmentioning
confidence: 99%